DIFERENCOVANÉ ZPŮSOBY OBSLUHY VE VEŘEJNÉ OSOBNÍ PŘÍMĚSTSKÉ DOPRAVĚ – OD NASAZENÍ TAXI K ŘÍZENÉ MOBILITĚ (Perner's Contacts, 2007)
The paper deals with a problematic of different service forms in public passenger suburban transport, scilicet from taxi-cab implementation to controlled mobility. The paper defines several service types starting with express or speed buses, disco buses, cycle buses and ending with call-line taxi-cabs or call-accumulating taxi-cabs etc. The paper deals in the end with a problematic of controlled mobility as last step of mobility management.
Keywords: traffic service; mobility management; special bus